WWW.DISSERS.RU


...
    !

 >> 
pj j =1, 2 + + h3-j pj x, y, t = hj j G(r)+ G0(r) dx dy + h3-j 3-j G(r) - G0(r) dx dy. hj - - G(r) =(1/2)lnr, G0(r) =-(1/2)K0(r) 2 2-2 j(x, y, t) 2 2 hj r = x - x + y - y K0(z) = R/Rd R Rd Aj j =j0 + x, y, t, j =1, 2, j =1 j0 j Sj Aj Sj j Aj h3-j pj = pj0 + hj W M(r) + M0(r) d+ j hj =1 Cj A3-j h3-j M(r) - M0(r) d, j =1, 2. 3-j =1 C3-j Cj Sj (x - x)(y /) - (y - y)(x /) r2 1 W =, M = ln r -, r2 4 2 1 M0 = rK1(r) - 1 ; 22 = 1 1 = 2 = 5 1 = 5, 2 = 0 1 = -2 =5 Cj pj0 j0 A1 = A2 = 1 R1 = R2 R 1 1 1 1 2 2 2 2 Vj r = Vp(R) hkk - h3-jV(R) (-1)j-kk, j =1, 2, k=1 k=1 r/R, r R, R Vp(R) = 2 R/r, r > R;

K1 R I1 r, r R, V(R) = R I1 R K1 r, r > R.

K1(z) I1(z) rj = fj , t; R, R = fj , 0; R, j =1, 2, fj , t; R = R + jexpim(-t), j =1, 2, |j| R, m 1, m Im > 0 j pj0 j lim Sj = , j j 0 Sj j Sj = x - x y - yj, j j j pj0 =0 Aj A3-j hj h3-j h3-j pj (x, y) = ln r - K0(r) + ln r + K0(r), j =1, 2, j 2 hj hj 3-j =1 =1 2 2 r = x - x + y - yj = 1/Rd j Aj yj hj - yj h3-j = - 1+ rjj K1 rjj + j j 2 hj (rjj )2 =1 = A3-j yj h3-j - y3-j 1 - rj(3-j)K1 rj(3-j), 3-j hj (rj(3-j))2 =1 Aj x hj j - x h3-j j = j 1+ rjj K1 rjj + j 2 hj (rjj )2 =1 = A3-j x h3-j j - x 3-j 1 - rj(3-j)K1 rj(3-j). 3-j hj (rj(3-j))2 =1 2 2 rij = x - x + yi - yj =1, 2,..., Aj; j =1, 2 i j Aj Aj 2 2 Q = hj , Px = hj x, j j j j=1 =1 j=1 =1 Aj Aj 2 2 2 2 Py = hj yj , M = hj x + yj j j j j=1 =1 j=1 =1 x, y H H qj = J qj, H, = - J p, H, j j p qj j =1, 2,..., Aj; j =1, 2, qj = x p = yj /2 j j j Aj 2 1 h3-j H = - hj ln rjj - K0 rjj + j j 2 hj j=1 ,=1 = Aj, A3-j h3-j ln rj(3-j) + K0 rj(3-j) hj j 3-j , =1 M H (Px)2 +(Py)2 Q = Px = Py =0 l L = l 1+LK1(L) f1(L) v = = 4L 4 1 - LK1(L) f2(L) f2 A1 = A2 = A 1 2 =... A - 1 2 =... A >0 1 1 1 2 2 2 A A A 2( - 1) 2( - 1) x = r(t)cos j(t) +, yj = r(t)sin j(t) +, j A A r, j j =1, 2 =1, 2,..., A A-1 A-1 A = - s 0, A - r s , 0 S , 0 + s , S , , 4r 2 =1 =0 A-1 A-1 1 = - + r S , 0 + S , , 4r2 2 =1 =0 L = L f2(L) = 3-j - j 2c sin + d c A sin + d 2r sin c d K1 s c, d =, S c, d = +.

2c A 2 A 2 1 - cos + d A A R, , A =ln R sin + K0 2R sin + 2 2 A-1 K0 2R sin + K0 2R sin + = const, A A 2 =1 R = r A =3 A =6 = /A, (x, y) A A =3 =1 A =6 =2 A-1 1 = S 0, + S , 0 + S ,.

2R A A =1 A [3; 5] A A 6 A = 2 A A =2, 3,..., 12 Z A =2 (x, y) =2 =1 =0.1 Z A1 = 1 A2 = A 2 1 = , , = 1 2 1, 2,..., A A 1 x1 = y1 =0, 1 2( - 1) 2( - 1) x; y2 = r cos + ; sin +, =1, 2,..., A, 2 A A r A-1 = - cos K1 2r sin 0, 4 A A =1 A-1 A - 1 = + 1 - rK1(r) + r sin K1 2r sin. 4r2 2 A A =1 = 1 - A /2 -1/2 R0 1 - A /2 -1/2. R < R0 R > R0 A = 2 = -2 A =2 RR A = 2, = 1, = -2 R>R0 R = R0 R

1 2 2 1 1 2 1 2 1 + +.

1 2 2 1 2 2 1 2 1 +.

2 2 1 j j = -2.5 1 1 1 2 2 2 X (Xc, 0) = -2 h11+h22 =0 m 1 m = (1 - 2h1) L1() - Lm() m(, h1), 2(1 - h) 2h1(1 - h1) m(, h1) = L1() - Lm() L1() - (1 - 2h1)2Lm() -, m h1 h1+h2 =1 Lm() =Im()Km() m m 1 1 1 Lm() 0 Lm() .

2m 2 m m(, h1) =0 m m n > 2 n(h1) < (h1) < n+1(h1) m = 2, 3,..., n h1 = 0.5 2 = = 1.705 < h1=0.5 > h1, |Imm| h1 =0.5 m hj j j = 1, 2 j h1 m m. h1=0.5 =4 m =3 m = 3 m =3 Rd =14 m =9 Rfr h =0.5 =14 m =2, 3,..., 11 Rfr Rfr R t1/2 R t A S R Rmin m m S Rmin(m) m, 2.7. S R > Rmin(m) m m m V1 V2 =0 =2 h1 =0.5 =0.5 =0.5 =2 h1 =0.25 =0.825 = -1 =3 h1 =0.5 =0.84 = 2 h1 = 0.5 = 0.5 x a/b = 1.05 =0 =2 h =0.5 =0.5 =2 h =0.25 = 0.5 =0.5 =2 h =0.25 =0.825 = -1 = 3 h = 0.5 = 0.84 m =1 m =2 S U (, d) d <1.705 1.705 < 2.5 d [ >2.5; 0.0

 >> 





2011 www.dissers.ru -

, .
, , , , 1-2 .